Biocapacity in the Gili Matra Region: A Spatial Assessment of The Carrying Capacity of Small Islands - Fery Kurniawan; Luky Adrianto; Dietriech G. Bengen; Lilik Budi Prasetyo (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
Spatial as a contributor to biological productivity and ecosystem services have not been considered in the sustainable development of small islands. The aim of this study to appraise biocapacity (BC) in the Gili Matra Islands to estimate the existing carrying capacity for sustainable development, and refines the current BC methodology that emphasizes the spatial aspects in small islands. Based on analysis results, the Gili Matra Islands have BC total ranging from 659.46 to 1,069.57 gha in 2010, and increased from 673.64 to 1,093.02 gha in 2014. The highest total BC is the Gili Trawangan Island, while the lowest is the Gili Meno Island, but for the local BC is the opposite. The total local BC per island can be supplied around 0.00857 gha per capita for the Gili Ayer Island, 0.20103 gha per capita for the Gili Meno Island, and 0.00344 gha per capita for the Gili Trawangan Island. They are influenced by population density. The BC values indicate a critical position, both per-unit-area or per-capita, which is spatially nearly 100 % of the needs supplied from outside the island, and demonstrate the use on the Gili Matra Region have exceeded the existing carrying capacity. The sustainable development aspects and land use management should be applied strictly to ensure the sustainability of natural resources, social and economic, as well as cotinuously consider the efforts and existing strategies of conservation. The export and import factors of bioproductivity should be considered in making long-term planning. Spatially, BC appraisal was applicable to illustrate the condition of an area on the small islands. The GIS based BC can give the information of pattern of changes and distributions, both spatial and temporal. However, the statistical data use is needed to get the value of BC per capita.